Tasawuf Pesantren: Jalan Menuju Revolusi Spiritual - Lalu Pattimura Farhan; Prosmala Hadisaputra (Al-Fikr: Jurnal Pendidikan Islam, 2020)
This article is guided by one core question, which is how pesantren revolutionized spirituality through Sufism. To answer these questions, the authors collected literature from the Google search engine and Google Scholar. In the search for literature, the author found that studies of the spirituality revolution can be said to be very little, while studies of mental revolution can be considered a lot. The literature taken by Google Scholar shows that the mental revolution is more popular than the spirituality revolution in Indonesia. However, the author holds that the two terms have the same goal, which is to improve morality, which is totally integrated with all aspects of individual life. This article concludes that there are six forms of approach to the spirituality revolution in pesantren, namely: First, the cultivation of the values ​​of Sufism in the field of business and entrepreneurship (entrepreneurship). Second, the acquisition of spirituality through Sufism is done by listening to music. Third, the tarekat is implemented for the rehabilitation of drug patients. Fourth, the tarekat is implemented for mental patients. Fifth, tarekat is used for trauma healing. Sixth, studies and practices of Sufism are broadcast online.